Studying of capability of lactic acid bacteria to utilize a grain shot from brewing industry - Каирова, М.Ж. (Fundamental and Experimental Biology, 2015)
It is shown that studied strains could grow on a mediumwith aqueous extract of the grain shot and a titer of bacterial cells was higher in two times on the medium with 100 % of aqueous extract. Strains of lactic acid bacteria are produced L-lactic acid in 4,3–5,0 мМof concentrations. 0025 RKM strain had high activity and can produce 5,5 мМof concentration of L-lactic acid.